(untitled) (Journal of Hama University, 2022)
Social networking sites are an educational tool that includes many students in various disciplines and a site to promote various ideas, and the university students category is one of the most used groups for this site, and its bad use may lead to addiction and turn it into a tool that threatens the future of students. Assessment of addiction of social networking sites among students of the Faculty of Nursing at the University of Hama. A descriptive cross-sectional study was performed on a convenience sample of 100 students from the College of Nursing at the University of Hama, data was collected by a structured questionnaire which was developed by the researcher. The results of current study showed that 95% of the students have an account on one of the social networks, and that 68% of them prefer social networks to mingle with people during their spare time, and 69% believe that one of the advantages of social networking sites is the possibility of benefiting from it in the ability to fetch information from the sites The instruction is at a lower cost, and 80% believe that neck and back pain are among its downsides. There should be conducting of continuous programs that educate the students about the importance of social networks as one of the latest developments in technology and the necessity of using them in educational aspects in a safe and sound manner, establishing interactive websites in universities and educational institutions on which specialists are based in order to adopt the ideas of young people and direct them according to sound foundations and address any wrong ideas that arise.